Keefektifan Konseling Kelompok Dengan Teknik Cognitive Restrucuring Untuk Mengurangi Sadfishing Pada Mahasiswa - Tabrani Sanjaya; Manah Rasmanah; Hartika Utami Fitri (CV. ITTC INDONESIA, 2024)
restructuring techniques to reduce sadfishing in students. The method in this study used in this study is quantitative method, using the type of experimental research. The population in the implementation of this research is the students of the Islamic Counseling Guidance Study Program class of 2020, consisting of 141 people. The sampling technique in this study uses the Purpuse Sampling system with predetermined criteria, namely Islamic Counseling Guidance Students class of 2020, High and medium sadfishing categories and Willing to be voluntary participants in this study. Data collection techniques use questionnaires, while data analysis uses the Wilcoxon Test. From the results of this study concluded that the experimental group experienced a decrease in the level of sadfishing Prestest (mean) 87 after tretment with group counseling with cognitive restructuring techniques with Postest results (mean) 67. While the control group that did not use cognitive restructuring techniques Prestest mean 83 and postest results 81. The Wilcoxon test shows a 2-tailed, Asymp.sig (2-tailed) value, 018. The value of 018 <0.05, it can be concluded that Ha is accepted and Ho is rejected, means that it has a difference from the results of Prestest and Posttest. So it was concluded that group counseling with cognitive restructuring techniques is effective in reducing sadfishing in students.Keywords: Group Counseling, Cognitive Restructuring , sadfishing